STOCK PRICE REACTION ANALYSIS TO THE COVID-19 PANDEMIC (EMPIRICAL STUDY OF INDONESIA STOCK EXCHANGE LISTED COMPANIES IN 2020) - Fifitri Ali; Yolanda Marlina ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2021)
This study aims to determine the reaction of stock prices to the announcement of the first patient of Covid-19 in Indonesia on the Indonesia Stock Exchange (BEI). This research was conducted at all companies listed on the IDX during the study period. All companies studied were divided into nine sectors which were classified according to the industrial classification set by the BEI, namely JASICA (Jakarta Industrial Classification). The event study method is used to test the stock price reaction to these events. Based on the research results, there are significant stock price reactions on the nine Sectoral Indices on the IDX, namely the Agri Sector; Mining; Basic-Ind; Misc-Ind; Consumer; Property; Infrastructure; Finance and Trade, while for the Sectoral Index that suffered the most losses, namely Property from the announcement of the first Covid-19 patient in Indonesia.